Intrinsic Value Estimation Through Fundamental Analysis: A Case Study of Dr. Reddy’s Laboratories Ltd., Hyderabad - Viswanatha Reddy, C.; Viswa Pavani, J. (Indian Journal of Finance, 2012)
Fundamental analysis is a stock valuation method that uses financial and economic analysis to predict the movement of stock prices. It is a process of looking at a business at the fundamental financial level. It is a three-step examination, which calls for understanding the macro-economic environment and developments, analyzing the prospects of the industry to which the firm belongs, assessing the projected performance of the company. Company analysis for the estimation of intrinsic value can be organized in two parts (a) a study of financials, and (b) a study of other factors. However, the researchers have restricted to the study of financials only and have not focused on other factors. There are two principal methods of equity valuation, viz., the dividend discount model and the earnings multiplier model. In practice, the earnings’ multiplier method is the most popular method. The key questions to be addressed in applying the earnings multiplier approach are: What is the expected EPS for the forthcoming year? What is a reasonable P/E ratio given the growth prospects, risk exposure, and other characteristics of the firm? To answer these questions, investment analysts start with a historical analysis of earnings (and dividends), growth, risk, and valuation and use this as a foundation for developing the forecasts required for estimating the intrinsic value.